2022
DOI: 10.1097/md.0000000000029998
|View full text |Cite
|
Sign up to set email alerts
|

Association between chronic pain with presarcopenia and central sensitization in Japanese community-dwelling older adults: A cross-sectional study

Abstract: Older people with chronic pain are at higher risk of developing sarcopenia. Central sensitization (CS) has been implicated in chronic pain among community-dwelling older adults. However, a relationship between CS and chronic pain with sarcopenia has not been established. This cross-sectional study aimed to clarify the relationship between chronic pain with sarcopenia or presarcopenia and CS among community-dwelling older adults. We assessed chronic pain and sarcopenia in 104 older adults participating in commu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…The list of excluded studies and their respective reasons of exclusion is available on our Open Science Framework deposit (https://osf.io/rqhvy/). Therefore, a total of 43 observational studies were included in this systematic review, 42 cross‐sectional studies 5,27–67 and one prospective study 68 for which baseline values of HRQoL for the sarcopenic and non‐sarcopenic groups were used (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…The list of excluded studies and their respective reasons of exclusion is available on our Open Science Framework deposit (https://osf.io/rqhvy/). Therefore, a total of 43 observational studies were included in this systematic review, 42 cross‐sectional studies 5,27–67 and one prospective study 68 for which baseline values of HRQoL for the sarcopenic and non‐sarcopenic groups were used (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…Increased lean muscle mass is known to be associated with reduced migraine frequency [64,65]. Moreover, increment/preservation of lean body mass has been shown to combat central sensitization in chronic pain syndromes [66]. This indicates that the type of weight loss determines the efficacy of exercise interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Prevalence data for sarcopenia were extracted from 11 remaining studies (n=29,832), 13,16,17,20,[22][23][24][25][26]29,30 yielding a cumulative prevalence of 0.11 (95% CI, 0.08-0.14) (Figure 2). Subgroup analysis revealed a slightly higher prevalence of sarcopenia in low-and middle-income countries (0.12, 95% CI, 0.09-0.16) than in high-income countries (0.11, 95% CI, 0.07-0.15).…”
Section: Prevalence Of Sarcopenia Among Older Adults With Chronic Painmentioning
confidence: 99%
“…11 Furthermore, there appear to be shared pathophysiological mechanisms between sarcopenia and chronic pain, such as elevated circulating levels of pro-inflammatory factors and oxidative stress. 12,13 The relationship between sarcopenia and chronic pain has not yet been clearly elucidated. Studies have shown that people with sarcopenia tend to report higher rates of pain compared to non-sarcopenic populations.…”
Section: Introductionmentioning
confidence: 99%